Computational Investigation of Catalyzed Organic Reactions: Metal- and Organo-Catalysis, Bio-Catalysis and Carbo-Catalysis - Giacinto, Pietro <1980> (Alma Mater Studiorum - Università di Bologna, 2016)
In this thesis the results of a Computational Organic Chemistry Ph.D. work course ranging from organometallic to metal-free and enzymatic catalysis is discussed. Various energetic and mechanistic aspects of organic reactions in catalysis are the key-issues which are addressed. A multidisciplinary approach allowed the development of several research projects in collaboration with experimental groups and combined experimental-theoretical works were carried out. Notes and comments concerning the theoretical models used and the experimental work carried out by the research groups who cooperated with us, are reported. The thesis comprises four main sections. The first section provides basic information on the computational methods used in the present work. In the subsequent sections (Part II, Part III and Part IV) we focus on different aspects of organic catalysis. In Part II the results of computational studies on the mechanism of various metal-catalyzed reactions are presented. In particular we describe organic reactions catalyzed by Gold(I) complexes. We consider some synthetically important processes in organic chemistry. The purpose of these studies was to discover some general rules to rationalize the role of gold complexes in different classes of organic reactions. Furthermore, at the end of this section we describe a mechanistic investigation of an example of organo-catalysis, thus not involving metal complexes. In Part III we focus on an emerging and promising area of "metal-free" catalysis, based on carbon nanostructures such as graphite, graphene, graphene oxide, fullerenes and carbon nanotubes (CNTs). This “metal-free” catalysis is usually denoted as Carbocatalysis. The energy contributions that may influence the course of a reaction inside a CNT, have been elucidated by means of computational methods. In Part IV the computational approach is used to elucidate the mechanism of an enzymatic reaction. We describe the results obtained in the study of tyrosine O-sulfonation catalyzed by human Tyrosylprotein Sulfotransferases-2.